HUBUNGAN TINGKAT PENGETAHUAN DENGAN MOTIVASI UNTUK BERHENTI MEMAKAI NAPZA PADA REMAJA DI PONPES SURYALAYA SURABAYA - Nur Hidaayah; Nila Armiati Fitrianingrum (Universitas Nahdlatul Ulama Surabaya, 2013)
The number of drug abusers has been increasing rapidly from year to year, so it can be considered to endanger the safety of the nation's next generation. The research was Purposed to analyze the relationship of knowledge and motivation to stop drug use in adolescents at boarding school students Suryalaya Korwil Inabah XIX Surabaya in East Java. The design of this research is correlational by nature analytical cross sectional approach. Population of all students at boarding school teen Suryalaya Korwil Inabah XIX Surabaya in East Java as much as 24 people until found 22 respondent. Sampling technique is simple random sampling. Instrument using a questionnaire. Processing of test data used was spearman rank through SPSS with significance level α = 0.05. Teenager in boarding school students Suryalaya Korwil Surabaya in East Java Inabah XIX obtained in the majority of students have good knowledge Inabah with half of the respondents have a high motivation. From the results of statistical tests in getting ρ <α is 0.002 <0.05 which means that Ho is rejected or no relationship between level of knowledge and motivation to stop drug use on adolescent students. Conclusion the study is the higher level of knowledge, the higher the motivation to stop drug use. The importance of nurses providing motivation to the youth about the effects of addictive drugs so they do not re use it.